Improving elementary students’ self-efficacy and achievement in mixed arithmetic operations through scaffolding (Diniyah: Jurnal Pendidikan Dasar, 2026)
Mixed arithmetic operations remain challenging for elementary students because they require procedural accuracy, conceptual understanding, and confidence in solving multi-step problems. This study aimed to examine the implementation of scaffolding strategies to improve sixth-grade students’ self-efficacy and mathematics learning outcomes. A classroom action research design was employed in one sixth-grade class at SD Negeri 1 Bogoran, involving 28 students. The study was conducted through a pre-cycle phase and two action cycles consisting of planning, acting, observing, and reflecting. Data were collected through a mathematics self-efficacy questionnaire, a mixed arithmetic operations test, classroom observation, and reflection notes. The findings showed consistent improvement across cycles. Students’ average self-efficacy score increased from 62.4 in the pre-cycle to 74.8 in Cycle I and 84.6 in Cycle II. Their average test score increased from 63.2 to 72.5 and 81.9, while classical mastery improved from 46.4% to 71.4% and 89.3%. These findings indicate that scaffolding supported students’ confidence, persistence, participation, and procedural understanding. The study implies that adaptive and gradually reduced scaffolding can strengthen both affective and cognitive outcomes in elementary mathematics learning. Keywords: classroom action research; elementary mathematics; mathematics learning outcomes; mixed arithmetic operations; scaffolding strategy; self-efficacy